Estudo do polimorfismo C2029T no gene do receptor toll-like tipo 2 e da resposta imune humoral em pacientes com hanseníase - Rodrigues, Aracélia Gurgel (2008)
Although several efforts from Ministry of Health have been made in order to eliminate leprosy, Brazil is still the second country with the highest number of cases in world after India and is responsible for 80% of the cases in the American continent, the Ceara state situated in the Norheastern region is considered to have high incidence rates of leprosy cases. According to Ridley and Jopling classification, the clinical forms of leprosy can be divided in lepromatous leprosy, borderline lepromatous leprosy, borderline borderline leprosy, borderline tuberculoid leprosy, and tuberculoid leprosy. This work was done with 87 patients with leprosy, being 51.72 % of the female gender and 48.3% of the male gender; from the total of patients, 77.0% had been vaccinated with BCG once in life. All the patients enrolled in the study were not treated (n=23) or in treatment (n=64). Most of the patients had suffered from leprosy for the first time and some (n=11) had suffered from leprosy recidive. The anti-PGL1 serum IgG serology has been performed in 83 patients, and the most significant differences were found comparing the tuberculoid leprosy and borderline tuberculoid leprosy groups with the borderline lepromatous leprosy group. All DNA samples (n=87) were amplified in respect to the 171 bp highly conserved sequence of the aminoacids 671-692 from the C-terminal intra-cellular domain of Toll-like 2 receptor, and they were submitted to a Single Strain Conformation Polymorphism Technique (SSCP). The eletrophoretic profile found of the samples showed two and three bands, it is essential to the sequencing, this showed heterozygosis at position C2029T, and in addition two other sections of heterozygosity at positions C2006T (found in all four sequenced samples) and 2008 (sample 82). The work showed that the heterozygosity found in the gene exon 3 of the tool-like receptor type 2, unlike the one found by Kang and Chae (2001) which may mean that the susceptibility profile from our population is distinct from those found in India and Korea.